DYNAMIC PARAMETERS CERTIFICATION FOR ASYNCHRONOUS FSM - Galupa, Nicolae (European Scientific Journal, ESJ, 2014)
Although the use of asynchronous sequential machines is confined to solving specific problems where synchronous machines are non-applicable or perform poorly, we can encounter many situations where we definitely wish to exploit their benefits (high speed, low resolution time,…, etc.). However considering the fact that these asynchronous sequential machines are integrated with synchronous machines, a minimal output signal width must be provided in order to obtain the needed control capability. A control method for the output signal width is presented and experimental results confirm its validity. This method represents in fact a hybrid asynchronous model.